2019
DOI: 10.1017/s1041610219000772
|View full text |Cite
|
Sign up to set email alerts
|

The Dunedin dementia risk awareness project: pilot study in older adults

Abstract: Aims:The USA and UK governmental and academic agencies suggest that up to 35% of dementia cases are preventable. We canvassed dementia risk and protective factor awareness among New Zealand older adults to inform the design of a larger survey.Method:The modified Lifestyle for Brain Health scale quantifying dementia risk was introduced to a sample of 304 eligible self-selected participants.Results:Two hundred and sixteen older adults (≥50 years), with mean ± standard deviation age 65.5 ± 11.4 years (50–93 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Stewart et al (2014) examined the difference in the prevalence of dementia in different types of nursing homes, revealing an overall prevalence of around 75% dementia (10% mild dementia, 25% moderate dementia and 40% severe dementia), with the lowest prevalence in homecare. Modifiable risk factors for dementia include smoking, lack of physical activity, depression, poor memory training, and social isolation, the latter being the largest factor (Barak et al, 2019). Isolation and loneliness are significant risk factors for the development and progression of dementia.…”
Section: Dementiamentioning
confidence: 99%
“…Stewart et al (2014) examined the difference in the prevalence of dementia in different types of nursing homes, revealing an overall prevalence of around 75% dementia (10% mild dementia, 25% moderate dementia and 40% severe dementia), with the lowest prevalence in homecare. Modifiable risk factors for dementia include smoking, lack of physical activity, depression, poor memory training, and social isolation, the latter being the largest factor (Barak et al, 2019). Isolation and loneliness are significant risk factors for the development and progression of dementia.…”
Section: Dementiamentioning
confidence: 99%
“…Our outcome measures had a high face validity. Furthermore, similar measures were also used in other recent studies (8,11). Nevertheless, our findings are based on cross-sectional data and should be validated by using longitudinal data, and based on more elaborated scales (for example, see the questionnaire used in the study conducted by Heger et al (9).…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…With regard to the perception that memory deterioration is preventable (second outcome measure of our current study), only one recent study of individuals 50 years or older found that individuals show optimism about modifying dementia risk through lifestyle interventions (n = 216) (8). We are not aware of other studies investigating this outcome.…”
Section: Previous Research and Possible Explanationsmentioning
confidence: 85%
See 1 more Smart Citation
“…Qualitative studies conducted in the UK12 13 and elsewhere in Europe14 showed varying awareness of actions beneficial for the brain, and emphasised the importance of providing people with evidence-based and trustworthy information to encourage adoption of brain-friendly behaviours. Studies conducted in Australia and New Zealand have also reported limited knowledge about cognitive health and Alzheimer’s disease (AD)15 and potential measures to reduce risk of dementia and cognitive decline 16–19. A 2015 systematic review of public perceptions about risk and protective factors for cognitive health and impairment concluded that although some awareness was present regarding risk factors for cognitive impairment, efforts should be made to provide the general public with accurate information regarding risk-reducing strategies 20…”
Section: Introductionmentioning
confidence: 99%